Rapid thinning of the Laurentide Ice Sheet in coastal Maine, USA, during late Heinrich Stadial 1. (1st May 2017) - Koester, Alexandria J.; Shakun, Jeremy D.; Bierman, Paul R.; Davis, P. Thompson; Corbett, Lee B.; Braun, Duane; Zimmerman, Susan R.
Abstract: Few data are available to infer the thinning rate of the Laurentide Ice Sheet (LIS) through the last deglaciation, despite its importance for constraining past ice sheet response to climate warming. We measured 31 cosmogenic 10 Be exposure ages in samples collected on coastal mountainsides in Acadia National Park and from the slightly inland Pineo Ridge moraine complex, a ∼100-km-long glaciomarine delta, to constrain the timing and rate of LIS thinning and subsequent retreat in coastal Maine. Samples collected along vertical transects in Acadia National Park have indistinguishable exposure ages over a 300 m range of elevation, suggesting that rapid, century-scale thinning occurred at 15.2 ± 0.7 ka, similar to the timing of abrupt thinning inferred from cosmogenic exposure ages at Mt. Katahdin in central Maine (Davis et al., 2015). This rapid ice sheet surface lowering, which likely occurred during the latter part of the cold Heinrich Stadial 1 event (19–14.6 ka), may have been due to enhanced ice-shelf melt and calving in the Gulf of Maine, perhaps related to regional oceanic warming associated with a weakened Atlantic Meridional Overturning Circulation at this time. The ice margin subsequently stabilized at the Pineo Ridge moraine complex until 14.5 ± 0.7 ka, near the onset of Bølling Interstadial warming. Our 10 Be ages are substantially younger than marine radiocarbon constraints on LIS retreat in the coastal lowlands, suggesting that the deglacial marine reservoir effect in this area was ∼1, 200 14 C years, perhaps also related to the sluggish Atlantic Meridional Overturning Circulation during Heinrich Stadial 1. Highlights: 10 Be dipstick suggests rapid ice sheet thinning at 15.2 ± 0.7 ka in coastal Maine. The ice margin stabilized at the Pineo Ridge moraine complex until 14.5 ± 0.7 ka. Deglacial marine reservoir effect was ∼1, 200 14 C years in coastal lowlands.